PENGARUH KUALITAS HARGA DAN PROMOSI PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINERAL DALAM KEMASAN (AMDK) MEREK AQUA - Muhammad Dwi Setiawan (Program Studi Akuntansi, 2022)
The purpose of this study was to test and determine the significance of the effect of product quality, product price, and promotion partially and simultaneously on the purchase decision of aqua branded bottled water. This research is a quantitative research. Data collection techniques using a questionnaire. The data analysis technique used descriptive statistical analysis, the classical assumption test consisted of normality, multicollinearity, and heteroscedasticity tests, and multiple regression tests. The results showed that; (1) quality has a positive and significant effect on purchasing decisions for branded aqua bottled water, the value of tcount = 2.632 > rtable = 1.987 with a significance value of 0.010 <0.05. (2) The price of the product has a positive and significant effect on the decision to purchase bottled water for the Aqua brand, the value of tcount = 2.460 > rtable = 1.987 with a significance value of 0.016 <0.05. (3) Promotion has a positive and significant effect on the decision of the aqua brand bottled drinking water, the value of tcount = 3.994 > rtable = 1.987 with a significance value of 0.000 <0.05. (4) Quality, price and promotion have a positive and significant effect on consumer satisfaction of branded aqua bottled water, the value of Fcount is 15,094 with a significance value of 0.000 <0.05. The value of Adjusted R2 is 0.299, which means that the product quality, price, and promotion variables are able to explain 29.9% of the variations that occur in the purchasing decision variables.